Hydrodynamics of Viscous Oil-Water Flow through Undulated pipelines - Desamata, Anand Babu (My University, 2014)
The flow of two immiscible liquids occurs commonly in petroleum industry, where crude oil and water produced from wells, are transported over long distances for subsequent separation and processing. In such cases, undulation of pipelines comprising of interconnected horizontal, upward and downward inclined sections are inevitable due to different elevation of the earth surface. Therefore, it is necessary to understand the different flow patterns and their transition boundaries for proper designing and sizing of a downstream separation and other unit of processing facilities. The majority of the past studies are confined to horizontal, inclined and vertical pipes of uniform cross-section. Not much is known about liquid flow across pipe network, although these are common occurrences in cross-country transportation. So an interest was felt to study the hydrodynamics of moderately viscous oil-water flow through a pipe network. Two networks have been selected in the present study: peak and valley configuration (Single unit of undulation is selected in both the cases). Due to the complexity of the undulated pipeline, first, experiments have been conducted in a simple horizontal pipeline to understand the hydrodynamics and the results are simulated using CFD. The objectives of the present work are as follows.
Mandal, Tapas K
Keywords: CHEMICAL ENGINEERING